Sensitivity and Specificity of Pleural Fluid Cytology to Histopathology Examination in Lung Tumor Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Kurniawan, Didy; Gama Satria; Dini Rizkie Wijayanti; Legiran (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction. Lung tumors are pathological growths in the lung that are strongly associated with lung cancer. In 2018, lung cancer, a form of lung tumor, had the greatest occurrence among all types of cancer. It accounted for 2,093,876 new cases, which represented 11.6% of all cancer cases. The objective of this study was to assess the sensitivity and specificity of pleural effusion cytology testing compared to histopathological examination in patients with lung malignancies at Dr. Mohammad Hoesin General Hospital in Palembang, Indonesia. Methods. This study was a retrospective analytical-observational study. This study encompassed a cohort of 35 patients who fulfilled the specified inclusion criteria. We used the SPSS version 22.0 for Windows application to perform bivariate analysis in data processing and analysis. Results. The study yielded a sensitivity score of 13.63%, indicating the pleural fluid cytology method's accuracy in detecting lung cancer in individuals with low values. This study demonstrates a specificity value of 100%, indicating the frequency at which the pleural fluid cytology approach accurately identifies cancer. Conclusion. The use of cytology as a screening tool for identifying lung tumor illnesses is limited, although it demonstrates a high level of specificity in ruling out healthy individuals.